استخدام المنتج الأخضر لقياس رضا المستهلكين (دراسة ميدانية على المنشآت الصِّناعيِّة في السَّاحل السوري) - زاهر بسام; الخير عبير (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدفُ هذا البحث إلى دراسة تأثير المنتج الأخضرفي تحقيق رضا مستهلكي منتجات المنشآت الصِّناعيِّة العاملة في السَّاحل السُّوري ومن ثمَّ تقديم مجموعة من المقترحات لإدارة هذه المنشآت بما يحسن من مستوى أدائها في السَّاحل السُّوري. اعتمدت الباحثة على الأسلوب الإحصائي وقامت بجمع البيانات الأولية من خلال استبيان كأداة للدراسة تمَّ تنظيمها بناءً على اطلاع الباحثة على الأدبيات المنشورة، حيث نظمت استمارتي استبيان، وزعت الاستمارة الأولى على عينة العاملين في المنشآت محل البحث في الإدارات الثلاث (عليا-وسطى-مباشرة) ووُزعت الاستمارة الثَّانية على عينة من مستهلكي منتجات المنشآت محل البحث، ومن أجل اختبار الفرضيات قامت الباحثة بتفريغ الاستبانات بقاعدة بيانات نظامية تمَّ تحليلها باستخدام برنامج SPSS/الإصدار رقم 20/ وقامت بحساب معامل ألفا كرونباخ لقياس ثبات المقياس، كما قامت الباحثة باختبار الفرضيات بالاعتماد على اختبار T لعينة واحدة، واختبار T لعينتين عندα=0.5. وتمثلَت أهم نتائج البحث بعدم وجود فروقات ذات دلالة بين متوسط عينة العاملين ومتوسط عينة مستهلكي منتجات المنشآت الصِّناعيِّة محل الدِّراسة حول تطبيق المنتج الأخضر، إضافة إلى ضعف في وعي المستهلك في السَّاحل السوري بالمنتج الأخضر، كما وأنَّه يعتبرأنَّ تلبية حاجاته ورغباته وجودة المنتج أكثر أهمية من المسؤولية البيئية. The objective of the research is to identifytheimpact of Green product in Achieving Consumer Satisfaction in industrial Institutionsoperating in the Syrian coast,finally provide a set of proposals for the management of these companies to improve their performance on the Syrian coast.The researcher adopted the statistical method,andthe preliminary data were collected through a questionnaire form as a tool for study, which was organized based on the researcher’s knowledge of published literature, where two questionnaires were organized, the first form was distributed to a sample of employees in the companies under consideration in the three departments (top, middle, Direct). The second questionnaire was distributed to a sample of consumers of the products of the companies in question. In order to test hypotheses, the researcher unloaded a database using SPSS issue 20 and adopted on Alpha Crompbach to measure the stability of the meter, the researcher also relied on a one-sample T-Test and Paired sample t-Test at α=0.5. The study comes up with the results that there were no significant differencesbetween sample of employees mean and sample of consumers mean in the industrial Institutionsin question, andthe view of consumers on the Syrian coast that meeting their needs, desires and productive quality is more important than environmental responsibility.